2011
DOI: 10.1111/j.1471-0528.2011.03018.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of polypropylene mesh anisotropy after implantation: an experimental study

Abstract: Please cite this paper as: Ozog Y, Konstantinovic M, Werbrouck E, De Ridder D, Mazza E, Deprest J. Persistence of polypropylene mesh anisotropy after implantation: an experimental study. BJOG 2011; DOI: 10.1111/j.1471‐0528.2011.03018.x. Objective  To determine whether anisotropy persisted after incorporation into the host, using a standardised rabbit model for abdominal wall reconstruction. Design  Investigator‐initiated prospective‐controlled experimental study. Setting  Centre for Surgical Technologies, Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…UltraPro, on the other hand, was found to display mechanical behavior that was vastly different depending on the loading direction. These results are similar to those previously reported (Saberski et al, 2011; Ozog et al, 2011), and confirm that it is important to consider the biomechanical properties of these grafts prior to implantation. Based on a co-rotational inverse finite element modeling approach, it was found that there is a significant degree of material nonlinearity inherent to each segment, but also that changes in mesh geometry could account for a large degree of structural nonlinearity and anisotropy observed experimentally for the UltraPro mesh.…”
Section: Discussionsupporting
confidence: 91%
“…UltraPro, on the other hand, was found to display mechanical behavior that was vastly different depending on the loading direction. These results are similar to those previously reported (Saberski et al, 2011; Ozog et al, 2011), and confirm that it is important to consider the biomechanical properties of these grafts prior to implantation. Based on a co-rotational inverse finite element modeling approach, it was found that there is a significant degree of material nonlinearity inherent to each segment, but also that changes in mesh geometry could account for a large degree of structural nonlinearity and anisotropy observed experimentally for the UltraPro mesh.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have focused on analyzing the effects of the anisotropy of a surgical mesh once implanted [8, 9,12]. However, the distensibility and stress produced to the tissues and implant cannot be experimentally addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Meshes were implanted via sacrocolpopexy in the Rhesus Macaque. Since UltraPro is highly anisotropic [7][8] , it was implanted with its blue orientation lines perpendicular (low stiffness direction) and parallel (high stiffness direction) to the longitudinal axis of the vagina. The production and degradation of collagen and elastin, collagen subtype III/I ratio as well as the levels of matrix metalloproteinases (MMP) MMPs -1, -2, -8, -9 and -13 were examined.…”
Section: Introductionmentioning
confidence: 99%